2008
DOI: 10.1001/archgenpsychiatry.2007.20
|View full text |Cite
|
Sign up to set email alerts
|

Higher Risk of Offspring Schizophrenia Following Antenatal Maternal Exposure to Severe Adverse Life Events

Abstract: Our population-based study suggests that severe stress to a mother during the first trimester may alter the risk of schizophrenia in offspring. This finding is consistent with ecological evidence from whole populations exposed to severe stressors and suggests that environment may influence neurodevelopment at the feto-placental-maternal interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
349
6
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 501 publications
(369 citation statements)
references
References 36 publications
8
349
6
6
Order By: Relevance
“…A male, but not female, fetus exposed during the second trimester of gestation to the stress of the 1940 invasion of The Netherlands had increased risk of schizophrenia later in life (van Os and Selten, 1998). This relationship between prenatal exposure to maternal psychosocial stress and risk for schizophrenia in male, but not female, offspring has been replicated in another study, but with first trimester exposure (Khashan et al, 2008). Although there are likely multiple factors contributing to sex differences in disease, sex-specific responses to fetal antecedents occurring during gestational sensitive windows may promote differences in programming trajectories that underlie such disease biases.…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 73%
“…A male, but not female, fetus exposed during the second trimester of gestation to the stress of the 1940 invasion of The Netherlands had increased risk of schizophrenia later in life (van Os and Selten, 1998). This relationship between prenatal exposure to maternal psychosocial stress and risk for schizophrenia in male, but not female, offspring has been replicated in another study, but with first trimester exposure (Khashan et al, 2008). Although there are likely multiple factors contributing to sex differences in disease, sex-specific responses to fetal antecedents occurring during gestational sensitive windows may promote differences in programming trajectories that underlie such disease biases.…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 73%
“…Studies on schizophrenia (13) indicated that the first trimester was the most vulnerable period, but studies on other endpoints suggested that the time window of susceptibility was in late pregnancy (12;35). Our findings suggest that exposure to severe stress during late pregnancy may have a greater influence on fetal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…The prenatal stress/schizophrenia association has been examined in several different ways. Death of spouse 31,32 and experience of catastrophic events, such as war 33 and nuclear explosion, 34 have been found to increase the risk of schizophrenia among those exposed. van Os and Selten 33 found an increased relative risk (RR) of schizophrenia (RR 1.28) among those in the Netherlands who were in their first or second trimester during the Nazi invasion in May 1940, and Malaspina and colleagues 35 found that those in their second month of gestation during the 1967 Arab-Israel War (Six-Day War) also had an increased risk of schizophrenia.…”
Section: Prenatal Stressmentioning
confidence: 99%
“…The association was present after accounting for both maternal depression and measures of fetal well-being at the time of the birth. Khashan and colleagues 32 found that death or serious illness of a relative during the first trimester was associated with an increased risk of developing schizophrenia, even when several potential confounders were controlled for. This partially replicates the classic finding of Huttunen and Niskanen.…”
Section: Prenatal Stressmentioning
confidence: 99%